Critical Evaluation of Green Synthesized Silver Nanoparticles-Kaempferol for Antibacterial Activity Against Methicillin-Resistant Staphylococcus aureus - Ariff Haikal Hairil Anuar; Siti Aisyah Abd Ghafar; Rohazila Mohamad Hanafiah; Vuanghao Lim; Nur Farah Atiqah Mohd Pazli (Taylor & Francis, 2024)
Indexed by WOS/Scopus/ERA